Facile template synthesis of water-soluble triazine-based Schiff base ligand bridged-coordination polymers of Co(ii), Ni(ii), and Cu(ii): structure, biomolecular interactions, and cytotoxic activity. (1st August 2019) - Parveen, Sheikdawood; Premkumar, Thathan; Nguyen, Hung Huy; Govindarajan, Subbiah
Abstract : For the first time, a new hydrazone Schiff base ligand and its Co(ii ), Ni(ii ), and Cu(ii ) complexes were synthesised and characterised. Their antioxidant and binding activities towards CT-DNA and BSA were evaluated. Abstract : A new set of water-soluble coordination polymers of Co(ii ), Ni(ii ), and Cu(ii ) with 3-(4-amino-3, 5-dioxo-2, 3, 4, 5-tetrahydro-[1, 2, 4]triazin-6-yl)-propionic acid ligand (HL) was synthesized and characterized. The powder X-ray diffraction (PXRD) pattern confirmed the isostructurality between Co(ii ) and Ni(ii ) complexes, whereas the Cu(ii ) complex had a slightly different coordination environment. The cobalt complex has octahedral geometry around the Co(ii ) ion, at which the triazine ligand (L) was coordinated via an O/N bidentate mode and bridged the two metal centres to form a one-dimensional polymeric unit, which was confirmed by single-crystal X-ray data. In vitro antioxidant assays with DPPH˙ (2, 2-diphenyl-1-picrylhydrazyl), ABTS˙ + [2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid diammonium salt)], NO˙ (nitric oxide), and O2 ˙ − (superoxide) radicals were performed to evaluate the free radical-scavenging ability and showed that the complexes in general and the Cu(ii ) complex in particular possess significant radical-scavenging activities compared to that of the ligand. The binding affinities towards biomolecules such as calf thymus DNA (CT-DNA) and bovine serum albumin (BSA) were determined, and the copper complex exhibited the highest activity. In addition, the complexes exhibited high cytotoxicity in human breast adenocarcinoma MCF-7 cells in vitro . Morphological changes and apoptosis were assessed using standard thiazolyl blue tetrazolium bromide (MTT) assay, semi-quantitative polymerase chain reaction (PCR) analysis, and acridine orange/ethidium bromide (AO/EB) and DAPI (4′, 6-diamidino-2-phenylindole) fluorescence staining assays.